Describing latent phase duration and associated characteristics among 1281 low‐risk women in spontaneous labor. Issue 4 (28th March 2019) - Tilden, Ellen L.; Phillippi, Julia C.; Ahlberg, Mia; King, Tekoa L.; Dissanayake, Mekhala; Lee, Christopher S.; Snowden, Jonathan M.; Caughey, Aaron B.
Abstract: Background: Recent research suggests that latent phase of labor may terminate at 6 rather than 4 centimeters of cervical dilation. The objectives of this study were to: (a) characterize duration of the latent phase of labor among term, low‐risk, United States women in spontaneous labor using the women's self‐identified onset; and (b) quantify associations between demographic and maternal/newborn health characteristics and the duration of the latent phase. Methods: This prospective study (n = 1281) described the duration of the latent phase of labor in hours, stratified by parity at the mean, median, and 80th, 90th, and 95th percentiles. The duration of the latent phase was compared for each characteristic using t tests or Wilcoxon rank‐sum tests and regression models that controlled for confounders. Results: In this sample of predominantly white, healthy women, duration of the latent phase of labor was longer than described in previous studies: The median duration was 9.0 hours and mean duration was 11.8 hours in nulliparous women. The median duration was 6.8 hours and mean duration was 9.3 hours in multiparous women. Among nulliparous women, longer duration was seen in women whose fetus was in a malposition. Among multiparous women, longer durations were noted in women with chorioamnionitis and those who gave birth between 41 and 41 + 6 weeks' gestation (vs between 40 and 40 + 6 weeks' gestation). Conclusions: The latent phase of labor may be longer than previously estimated. Contemporary estimates of latent phase of labor duration will help women and providers accurately anticipate, prepare, and cope during spontaneous labor.